Implementation Of Immigration Control Of Foreigners In The Context Of Deportation (Journal of Namibian Studies : History Politics Culture, 2023)
The purpose of this research is to know and analyse the implementation of supervision and deportation of foreign nationals and explain the factors that influence the implementation of supervision and deportation of foreign nationals at the Kendari Class I TPI Immigration Office.The research method used is non-doctrimal research method or empirical research by distributing questioners and interviews to respondents with stratified sampling, namely community leaders, academics and general immigration service users.The results showed that the essence of immigration control is the creation of law enforcement, through legal awareness, legal obedience to foreign nationals so that no legal deviations occur. The implementation of supervision and deportation of foreign nationals at the Immigration Office Class I TPI Kendari is based on the Immigration Law Immigration Supervision has not been implemented optimally. The factors that influence the implementation of supervision and deportation of foreign nationals at the Kendari Class I Immigration Office are legal structure factors, legal culture, legal equality and facilities and infrastructure factors.